THE EFFECTIVENESS SMART APPS CREATOR LEARNING MEDIA IMPROVING STUDENT LEARNING OUTCOMES IN THE ERA OF THE COVID-19 PANDEMIC - Herlan Perdana Putra; Elsje Theodora Maasawet; Muh. Amir Masruhim (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2021)
This study aims to design learning media smart Apps Creator, validity, practicality, and effectiveness on student learning outcomes using learning media Smart Apps Creator Android. This type of research is research and development (R&D) with the DDD-E development model. The output produced is the " My Ecosystem " application product from the development of SAC Android media on ecosystem materials with 4C ( Critical Thinking, Creativity, Collaboration, Communication). The results of the validity test showed 98% validity of learning media, 90.77% validity of the material, and 88% validity of language. The results of the practicality of my ecosystem media by teachers are 97% very practical and students, namely 89.1% very practical. So it can be concluded that my ecosystem media from the development of Smart Apps Creator Android in Biology learning is appropriate to be used as a learning medium and can improve student learning outcomes in online learning in the covid 19 era.